Une exploitation agropastorale gallo-romaine à Poupry “ Villeneuve ” (Eure-et-Loir) - Aurélien Hamel; Pierre Perrichon; Quentin Borderie; Justin Hahn; Yannick Mazeau (Revue Archéologique du Centre de la France)
Located 700 m west of the Roman road from Chartres-Autricum to Orléans-Cenabum, the agropastoral farm of “Villeneuve” in Poupry (Eure-et-Loir, France) was created in the second half of the 1st century AD at the latest, and abandoned at the end of the 2nd or at the beginning of the 3rd century AD. The excavation and the study of the archaeological furniture made it possible to distinguish three phases of occupation. The first one is characterized by the construction of a first 1,4 ha excavated enclosure. Its redevelopment at the end of the 1st or the beginning of the 2nd century AD materializes the next phase. The third phase (mid 2nd-early 3rd century AD) is defined by the gradual disaffection of the enclosure ditches. The spatial organization, mainly in perishable materials, evolves according these transformations. If agricultural buildings seem to have been clearly identified, the identification of the residential ones is more difficult. Similarly, the set of pits 1156 is problematic: extraction and/or manure pits?